2008
DOI: 10.1590/s1980-57642009dn20200002
|View full text |Cite
|
Sign up to set email alerts
|

Subcortical ischemic vascular disease and cognition: A systematic review

Abstract: Subcortical Ischemic Vascular Disease (SIVD) is underdiagnosed. This review investigates the relationship among SIVD severity, cognitive status and neuroimaging markers.MethodsCohort, cross-sectional and case control studies were searched on ISI, Medline, Scielo, PsychoInfo and LILACS databases published between 1995 and 2006.ResultsThe most impaired cognitive domains were executive, attentional and memory retrieval mechanisms. These cognitive features were frequently associated to White Matter Lesions (WML).C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 61 publications
0
3
0
2
Order By: Relevance
“…Currently, it is accepted that executive dysfunction is associated with the prefrontal-striatal pathway impairment. [ 13 ] The prefrontal-striatal pathway impairment may cause damage to the top-down control in the prefrontal lobe, resulting in executive dysfunction syndrome [ 16 ] which is characterized by abnormalities in the executive control, working memory, and dominant response inhibition as well as psychomotor retardation. Some studies propose that WML mainly affect the structure and function of prefrontal-striatal pathway [ 17 ] and disrupt the signal transduction between neurons and between prefrontal cortex and subcortical center, finally leading to the executive dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, it is accepted that executive dysfunction is associated with the prefrontal-striatal pathway impairment. [ 13 ] The prefrontal-striatal pathway impairment may cause damage to the top-down control in the prefrontal lobe, resulting in executive dysfunction syndrome [ 16 ] which is characterized by abnormalities in the executive control, working memory, and dominant response inhibition as well as psychomotor retardation. Some studies propose that WML mainly affect the structure and function of prefrontal-striatal pathway [ 17 ] and disrupt the signal transduction between neurons and between prefrontal cortex and subcortical center, finally leading to the executive dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this finding, researchers have proven over the years that patients with a history of stroke with large infarcts involving the cerebral cortex or the anterior and posterior arteries in the left hemisphere of the brain experience significant cognitive impairment in their memory functions, attention, orientation and language abilities (28). Researchers also believe that stroke can cause cognitive impairment, especially in areas of executive functioning, attention, memory and recall by the lesions it creates in the white matter (29). Researchers have also found that learning ability and verbal recall can be weakened even in patients with a mild stroke (30).…”
Section: Discussionmentioning
confidence: 95%
“…As a hallmark of SIVCI, 40 higher WMH is signi cantly correlated with poorer postural stability. 5,41 Hippocampal, WMH, and ICV were calculated and obtained from previous analysis.…”
Section: Structural Mri Analysismentioning
confidence: 99%